Synthesis of nanocrystalline spinel phase by mechanical milling of Al-Cu-Fe and Al-Cu-Cr-Fe quasicrystalline alloys - Mukhopadhyay N.K.; Yadav T.P.; Tiwari R.S.; Srivastava O.N. (My University, 2025)
In the present study, a low-temperature synthesis of (Cu,Fe)Al 2O4 and (Cu,Cr,Fe)Al2O4 spinels from the quasicrystalline phases was investigated with the variation of process parameters during milling and annealing. The milling of the quasicrystalline materials was carried out in an attritor mill at 400 rpm for 40 hours with ball to powder ratio of 40:1 in hexane medium. Subsequently, annealing was performed in an air ambience for 10, 20, and 40 h at 400, 500, 600 and 700 °C inside a furnace in order to oxidize the mechanically milled quasicrystalline phase for the possible formation of the spinel phase. It was found that after annealing at higher temperatures (∼500 °C), mechanically milled quasicrystalline alloy transformed to a spinel phase whereas annealing at lower temperatures (<500 °C) led to the formation of B2 phase as a major one along withminor amount of oxide phase. The X-ray diffraction and transmission electron microscopy of the annealed samples confirmed the formation of the spinel phase with an average grain size of ∼20- 40 nm. It is interesting to note that the nanospinel phases showed the different colors during various annealing time and temperature. The optical properties of nanospinel materials, investigated employing UV visible spectrometer exhibited absorption characteristics. © by Oldenbourg Wissenschaftsverlag.